Organizing Psychological Support to The Family - Tulkinboeva Makhliyo (European Science Publishing, 2023)
This scientific article talks about the types of psychological support for the family and the psychological ways of finding solutions to family problems.
Keywords: pedagogical skill, psychological training, woman, relationship, harmony, young family.